Risk factors for severe or fatal drug‐induced liver injury from amoxicillin–clavulanic acid. Issue 6 (7th October 2014) - Yazici, Cemal; Mutlu, Ece; Bonkovsky, Herbert L.; Russo, Mark W.
<x xml:space="preserve">Abstract</x> Aim To identify risk factors for severe liver injury or mortality from drug‐induced liver injury (DILI) from amoxicillin–clavulanic acid. To determine if co‐administration of potentially hepatotoxic drugs was associated with an increased risk of DILI from amoxicillin–clavulanic acid. Methods We conducted a systematic review of the published work and data extraction of articles on DILI injury from amoxicillin–clavulanic acid. Potentially hepatotoxic drugs were defined as medications with DILI listed in the package insert or reported in the published work. Individual patient data were entered into an SPSS (version 17.0; Chicago, IL, USA) database and were analyzed using the χ2‐test or Fisher's exact test; Student's t‐test; and non‐parametric tests such as Mann–Whitney U‐test as appropriate. Results We identified 3932 articles of which 41 publications with 255 reported cases met inclusion criteria. Mortality from DILI from amoxicillin–clavulanic acid was increased among patients receiving concomitant potentially hepatotoxic drugs compared with patients not on concomitant potential hepatotoxic drugs (21.4% [3/14] vs 2.3% [2/89], P = 0.017]. The most common classes of concomitant drugs were: antimicrobials, analgesics and hormonal therapy. Female patients were more likely to receive a concomitant potentially hepatotoxic medication (25% vs 9.1% for men, P = 0.05). Conclusion Patients who developed severe or fatal DILI from amoxicillin–clavulanic acid were more likely to be on concomitant hepatotoxic medications. Female patients were more likely to receive concomitant hepatotoxic drugs. Further studies are needed to investigate drug interaction between amoxicillin–clavulanic acid and concomitant potentially hepatotoxic drugs.